Preparation method of positive electrode material for improving first charge and discharge of lithium battery
Through the preparation of modified LiFePO4 materials, combined with the doping of Nb2O5 and single-layer Ti3C2MXene and the use of modified carbon sources, the problems of poor conductivity and poor circulation performance of lithium iron phosphate materials were solved, and the first charging and discharge of lithium batteries was significantly improved. Efficiency and cyclic stability.
Patent Information
- Application Number
- CN202411649414.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2024-12-31
AI Technical Summary
The poor conductivity, low theoretical capacity and poor circulation performance of lithium iron phosphate materials lead to insufficient first charge and discharge efficiency and stability of lithium batteries.
The LFP precursor was prepared by uniform mixing of LiOH, FeSO4·7H2O, and H3PO4. The LFP precursor was prepared by combining carbon black, Nb2O5 and single-layer Ti3C2MXene for mechanical calcination to form modified LiFePO4 material, and ferrocene methanol, polyethylene glycol, and acid chloride carbon black Reactively modify the carbon source to improve conductivity and structural stability.
It improves the cycle life of lithium batteries, reduces internal resistance, enhances the first charge and discharge efficiency and cycle stability, and improves the specific capacity and rate discharge performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of initial charge and discharge of lithium batteries, and in particular to a method for preparing a positive electrode material for improving initial charge and discharge of lithium batteries. Background Art
[0002] At present, the main cathode material for batteries in the domestic market is lithium iron phosphate, which is sought after by many battery manufacturers because of its environmental friendliness and low cost. Lithium iron phosphate is the first discovered and used olivine structure cathode material, and is also the first choice for energy storage batteries. Among them, O atoms form a hexagonal structure, and lithium atoms and iron atoms are located in the middle of the hexagon, forming FeO6 and LiO6 regular octahedral structures; however, lithium iron phosphate materials still have many shortcomings, such as poor conductivity, low theoretical capacity, poor cycle performance, etc. Therefore, how to solve these problems has become the research direction of many researchers.
[0003] In summary, it is of great significance to prepare a positive electrode material that improves the initial charge and discharge of lithium batteries. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a positive electrode material for improving the initial charge and discharge of a lithium battery, so as to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a positive electrode material for improving the initial charge and discharge of a lithium battery comprises the following steps: S1: Add LiOH, FeSO4·7H2O, and H3PO4 into deionized water, mix evenly, and bake to obtain LFP precursor; S2: The LFP precursor, carbon black, Nb2O5 and single-layer Ti3C2MXene material are fully mechanically mixed and calcined to obtain a modified LFP material; S3: The modified LFP material, the binder and the conductive agent are uniformly mixed, applied on an aluminum foil, and dried to obtain a positive electrode material.
[0006] More optimally, the molar ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1.
[0007] More optimally, in the LFP precursor, the mass ratio of the LFP precursor to Nb2O5 is (120~125):1, the mass ratio of the LFP precursor to the single-layer Ti3C2MXene material is (100~105):1, and the mass ratio of the LFP precursor to the carbon source is (90~95):1.
[0008] More optimally, the mass ratio of the modified LFP material, the binder and the conductive agent is 97:2:1.
[0009] The more optimized process conditions for the calcination are: in a nitrogen atmosphere, heating to 550°C-600°C at a rate of 30°C / min and calcining for 18 hours, and the annealing rate is 25°C / min.
[0010] Preferably, the carbon black is modified carbon black; the preparation method of the modified carbon black is as follows: (1) adding carbon black to a mixed acid solution for ultrasonic dispersion, heating to 90°C-100°C, reacting for 18-20 hours, cooling to room temperature, washing to neutrality, filtering, and drying, ultrasonically dispersing it in oxalyl chloride, adding N,N-dimethylformamide and stirring at room temperature for 2-3 hours, washing with tetrahydrofuran, and drying to obtain chlorinated carbon black; (2) adding chlorinated carbon black to dichloromethane for ultrasonic dispersion, adding ferrocene methanol and polyethylene glycol, uniformly mixing, adding triethylamine, heating to 50°C-55°C, reacting for 18-20 hours, purifying, and drying to obtain modified carbon black.
[0011] More optimally, the raw materials of the modified carbon black include the following components: by mass, 1-2 parts of acyl chloride carbon black, 0.1-0.15 parts of ferrocenium methanol, 0.7-1 parts of polyethylene glycol, 0.8-1.2 parts of triethylamine, and 25-30 parts of dichloromethane.
[0012] Preferably, the mass ratio of the N,N-dimethylformamide to oxalyl chloride is (3-6):1; and the molecular weight of the polyethylene glycol is 200-600.
[0013] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention prepares a LiFePO4 precursor by a conventional hydrothermal method; then the precursor is calcined with carbon black, Nb2O5, and a single-layer Ti3C2MXene to obtain a modified LiFePO4 material.
[0014] In the scheme, Nb 5+ The introduction of Fe doping into the Fe bit unit can effectively improve the migration efficiency of lithium ions and improve its cycle performance after long cycles; the introduction of a small amount of single-layer MXene material can not only effectively improve the battery conductivity and reduce the internal resistance, but also its surface F - The O-site units in the lattice can be doped to enhance conductivity by suppressing anti-site defects. Therefore, the modified LiFePO4 material not only has an improved cycle life, but also has improved internal resistance defects, which is beneficial to improving the initial charge and discharge efficiency of lithium batteries.
[0015] In order to improve the structural stability of LiFePO4 materials; in the scheme, a modified carbon source is obtained by reacting ferrocene methanol, polyethylene glycol, and acyl chloride carbon black; wherein polyethylene glycol has good affinity with LiFePO4, and it can improve the dispersibility of carbon black and Nb2O5, improve the structural stability of LiFePO4 positive electrode materials, thereby enhancing the cycle stability and discharge efficiency of the battery. Ferrocene is an organic metal compound with high conductivity, which can improve the conductivity of the positive electrode material, thereby helping to improve the specific capacity of the LiFePO4 positive electrode material. It can also act as a catalyst, which can affect the thermal stability of polyethylene glycol, making it easy to decompose, and increase the carbonization degree of polyethylene glycol, thereby improving the cycle stability and rate discharge performance of the battery. DETAILED DESCRIPTION
[0016] The following is a preferred implementation of the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. For ordinary technicians in this technical field, all other embodiments obtained by ordinary technicians in this field without creative work without departing from the principle of the embodiment of the present invention are within the scope of protection of the present invention.
[0017] In the following specific implementation methods, the parts are by mass. In this embodiment, it should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions. Examples include: Nb2O5 has a CAS number of 1313-96-8, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; the CAS number of single-layer Ti3C2MXene is 12363-89-2, purchased from Zhongke Materials; the binder is PVDF, model KF1100; the conductive agent is carbon black, model Super P; the molecular weight of polyethylene glycol is 400, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; the CAS number of ferrocene methanol is 1273-86-5, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; the CAS number of oxalyl chloride is 79-37-8, purchased from Shanghai Fuzhe Chemical Co., Ltd.; the CAS number of N,N-dimethylformamide is 68-12-2, purchased from Nantong Runfeng Petrochemical Co., Ltd.; the CAS number of tetrahydrofuran is 109-99-9, purchased from Shandong Yanshuo Chemical Co., Ltd.; the CAS number of triethylamine is 121-44-8, purchased from Jinan Jumeihui Chemical Co., Ltd.
[0018] Example 1: A method for preparing a positive electrode material for improving the initial charge and discharge of a lithium battery; S1: LiOH, FeSO4·7H2O and H3PO4 were placed in a reaction kettle, deionized water was added and mixed evenly, and the mixture was treated at 200°C for 16 hours, filtered and dried to obtain an LFP precursor; Among them, the molar mass ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1; S2: The LFP precursor, carbon black, Nb2O5 and single-layer Ti3C2MXene material were fully mechanically mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 600 ° C for 18 hours to obtain a modified LFP material; Among them, the mass ratio of LFP precursor to Nb2O5 is 125:1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 105:1, and the mass ratio of LFP precursor to carbon source is 95:1; The heating rate of calcination is 30°C / min, and the annealing rate of calcination is 25°C / min; S3: The modified LFP material, PVDF (KF1100), and conductive agent (Super P) were uniformly mixed in a mass ratio of 97:2:1, coated on a 12 μm aluminum foil, and dried at 120 °C for 12 hours to obtain a positive electrode material.
[0019] Example 2 Based on Example 1, the mass ratio of LFP precursor to Nb2O5 is 115:1; S1: LiOH, FeSO4·7H2O and H3PO4 were placed in a reaction kettle, deionized water was added and mixed evenly, and the mixture was treated at 200°C for 16 hours, filtered and dried to obtain an LFP precursor; Among them, the molar mass ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1; S2: The LFP precursor, carbon black, Nb2O5 and single-layer Ti3C2MXene material were fully mechanically mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 600 ° C for 18 hours to obtain a modified LFP material; Among them, the mass ratio of LFP precursor to Nb2O5 is 115:1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 105:1, and the mass ratio of LFP precursor to carbon source is 95:1; The heating rate of calcination is 30°C / min, and the annealing rate of calcination is 25°C / min; S3: The modified LFP material, PVDF (KF1100), and conductive agent (Super P) were uniformly mixed in a mass ratio of 97:2:1, coated on a 12 μm aluminum foil, and dried at 120 °C for 12 hours to obtain a positive electrode material.
[0020] Example 3 Based on Example 1, the mass ratio of LFP precursor to Nb2O5 is 120:1; S1: LiOH, FeSO4·7H2O and H3PO4 were placed in a reaction kettle, deionized water was added and mixed evenly, and the mixture was treated at 200°C for 16 hours, filtered and dried to obtain an LFP precursor; Among them, the molar mass ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1; S2: The LFP precursor, carbon black, Nb2O5 and single-layer Ti3C2MXene material were fully mechanically mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 600 ° C for 18 hours to obtain a modified LFP material; Among them, the mass ratio of LFP precursor to Nb2O5 is 120:1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 105:1, and the mass ratio of LFP precursor to carbon source is 95:1; The heating rate of calcination is 30°C / min, and the annealing rate of calcination is 25°C / min; S3: The modified LFP material, PVDF (KF1100), and conductive agent (Super P) were uniformly mixed in a mass ratio of 97:2:1, coated on a 12 μm aluminum foil, and dried at 120 °C for 12 hours to obtain a positive electrode material.
[0021] Example 4 Based on Example 1, the mass ratio of LFP precursor to Nb2O5 is 130:1; S1: LiOH, FeSO4·7H2O and H3PO4 were placed in a reaction kettle, deionized water was added and mixed evenly, and the mixture was treated at 200°C for 16 hours, filtered and dried to obtain an LFP precursor; Among them, the molar mass ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1; S2: The LFP precursor, carbon black, Nb2O5 and single-layer Ti3C2MXene material were fully mechanically mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 600 ° C for 18 hours to obtain a modified LFP material; Among them, the mass ratio of LFP precursor to Nb2O5 is 130:1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 105:1, and the mass ratio of LFP precursor to carbon source is 95:1; The heating rate of calcination is 30°C / min, and the annealing rate of calcination is 25°C / min; S3: The modified LFP material, PVDF (KF1100), and conductive agent (Super P) were uniformly mixed in a mass ratio of 97:2:1, coated on a 12 μm aluminum foil, and dried at 120 °C for 12 hours to obtain a positive electrode material.
[0022] Example 5 Based on Example 1, the mass ratio of LFP precursor to Nb2O5 is 135:1; S1: LiOH, FeSO4·7H2O and H3PO4 were placed in a reaction kettle, deionized water was added and mixed evenly, and the mixture was treated at 200°C for 16 hours, filtered and dried to obtain an LFP precursor; Among them, the molar mass ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1; S2: The LFP precursor, carbon black, Nb2O5 and single-layer Ti3C2MXene material were fully mechanically mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 600 ° C for 18 hours to obtain a modified LFP material; Among them, the mass ratio of LFP precursor to Nb2O5 is 135:1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 105:1, and the mass ratio of LFP precursor to carbon source is 95:1; The heating rate of calcination is 30°C / min, and the annealing rate of calcination is 25°C / min; S3: The modified LFP material, PVDF (KF1100), and conductive agent (Super P) were uniformly mixed in a mass ratio of 97:2:1, coated on a 12 μm aluminum foil, and dried at 120 °C for 12 hours to obtain a positive electrode material.
[0023] Example 6 Based on Example 1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 95:1; S1: LiOH, FeSO4·7H2O and H3PO4 were placed in a reaction kettle, deionized water was added and mixed evenly, and the mixture was treated at 200°C for 16 hours, filtered and dried to obtain an LFP precursor; Among them, the molar mass ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1; S2: The LFP precursor, carbon black, Nb2O5 and single-layer Ti3C2MXene material were fully mechanically mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 600 ° C for 18 hours to obtain a modified LFP material; Among them, the mass ratio of LFP precursor to Nb2O5 is 125:1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 95:1, and the mass ratio of LFP precursor to carbon source is 95:1; The heating rate of calcination is 30°C / min, and the annealing rate of calcination is 25°C / min; S3: The modified LFP material, PVDF (KF1100), and conductive agent (Super P) were uniformly mixed in a mass ratio of 97:2:1, coated on a 12 μm aluminum foil, and dried at 120 °C for 12 hours to obtain a positive electrode material.
[0024] Example 7 Based on Example 1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 100:1; S1: LiOH, FeSO4·7H2O and H3PO4 were placed in a reaction kettle, deionized water was added and mixed evenly, and the mixture was treated at 200°C for 16 hours, filtered and dried to obtain an LFP precursor; Among them, the molar mass ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1; S2: The LFP precursor, carbon black, Nb2O5 and single-layer Ti3C2MXene material are fully mechanically mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 550℃~600℃ for 18 hours to obtain a modified LFP material; Among them, the mass ratio of LFP precursor to Nb2O5 is 125:1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 100:1, and the mass ratio of LFP precursor to carbon source is 95:1; The heating rate of calcination is 30°C / min, and the annealing rate of calcination is 25°C / min; S3: The modified LFP material, PVDF (KF1100), and conductive agent (Super P) were uniformly mixed in a mass ratio of 97:2:1, coated on a 12 μm aluminum foil, and dried at 120 °C for 12 hours to obtain a positive electrode material.
[0025] Example 8 Based on Example 1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 110:1; S1: LiOH, FeSO4·7H2O and H3PO4 were placed in a reaction kettle, deionized water was added and mixed evenly, and the mixture was treated at 200°C for 16 hours, filtered and dried to obtain an LFP precursor; Among them, the molar mass ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1; S2: The LFP precursor, carbon black, Nb2O5 and single-layer Ti3C2MXene material were fully mechanically mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 600 ° C for 18 hours to obtain a modified LFP material; Among them, the mass ratio of LFP precursor to Nb2O5 is 125:1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 110:1, and the mass ratio of LFP precursor to carbon source is 95:1; The heating rate of calcination is 30°C / min, and the annealing rate of calcination is 25°C / min; S3: The modified LFP material, PVDF (KF1100), and conductive agent (Super P) were uniformly mixed in a mass ratio of 97:2:1, coated on a 12 μm aluminum foil, and dried at 120 °C for 12 hours to obtain a positive electrode material.
[0026] Example 9 Based on Example 1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 115:1; S1: LiOH, FeSO4·7H2O and H3PO4 were placed in a reaction kettle, deionized water was added and mixed evenly, and the mixture was treated at 200°C for 16 hours, filtered and dried to obtain an LFP precursor; Among them, the molar mass ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1; S2: The LFP precursor, carbon black, Nb2O5 and single-layer Ti3C2MXene material were fully mechanically mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 600 ° C for 18 hours to obtain a modified LFP material; Among them, the mass ratio of LFP precursor to Nb2O5 is 125:1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 115:1, and the mass ratio of LFP precursor to carbon source is 95:1; The heating rate of calcination is 30°C / min, and the annealing rate of calcination is 25°C / min; S3: The modified LFP material, PVDF (KF1100), and conductive agent (Super P) were uniformly mixed in a mass ratio of 97:2:1, coated on a 12 μm aluminum foil, and dried at 120 °C for 12 hours to obtain a positive electrode material.
[0027] Example 10 Based on Example 1, carbon black is modified by polyethylene glycol and ferrocene; S1: LiOH, FeSO4·7H2O and H3PO4 were placed in a reaction kettle, deionized water was added and mixed evenly, and the mixture was treated at 200°C for 16 hours, filtered and dried to obtain an LFP precursor; Among them, the molar mass ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1; S2: Preparation of modified carbon black: (1) Add carbon black to a mixed acid solution (the mass ratio of concentrated sulfuric acid to concentrated nitric acid is 1:8) for ultrasonic dispersion, heat to 100°C, react for 18 hours, cool to room temperature, wash until neutral, filter, dry, ultrasonically disperse it in oxalyl chloride, add N,N-dimethylformamide (the mass ratio of N,N-dimethylformamide to oxalyl chloride is 3:1), stir at room temperature for 2 hours, wash with tetrahydrofuran, and dry to obtain chlorinated carbon black; (2) Add 2 parts of chlorinated carbon black to 25 parts of dichloromethane for ultrasonic dispersion, add 0.12 parts of ferrocene methanol and 0.7 parts of polyethylene glycol (molecular weight 400), mix evenly, add 1.2 parts of triethylamine, heat to 55°C, react for 18 hours, purify, and dry to obtain modified carbon black; The LFP precursor, modified carbon black, Nb2O5 and single-layer Ti3C2MXene material were fully mechanically mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 600°C for 18 hours to obtain a modified LFP material; Among them, the mass ratio of LFP precursor to Nb2O5 is 125:1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 105:1, and the mass ratio of LFP precursor to carbon source is 95:1; The heating rate of calcination is 30°C / min, and the annealing rate of calcination is 25°C / min; S3: The modified LFP material, PVDF (KF1100), and conductive agent (Super P) were uniformly mixed in a mass ratio of 97:2:1, coated on a 12 μm aluminum foil, and dried at 120 °C for 12 hours to obtain a positive electrode material.
[0028] Comparative Example 1 is based on Example 1, in which Nb2O5 is not added; S1: LiOH, FeSO4·7H2O and H3PO4 were placed in a reaction kettle, deionized water was added and mixed evenly, and the mixture was treated at 200°C for 16 hours, filtered and dried to obtain an LFP precursor; Among them, the molar mass ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1; S2: The LFP precursor, carbon black, and single-layer Ti3C2MXene material were fully mechanically mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 600°C for 18 hours to obtain a modified LFP material; Among them, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 105:1; the mass ratio of LFP precursor to carbon source is 95:1; The heating rate of calcination is 30°C / min, and the annealing rate of calcination is 25°C / min; S3: The modified LFP material, PVDF (KF1100), and conductive agent (Super P) were uniformly mixed in a mass ratio of 97:2:1, coated on a 12 μm aluminum foil, and dried at 120 °C for 12 hours to obtain a positive electrode material.
[0029] Comparative Example 2 is based on Example 1, in which no single layer of Ti3C2MXene is added to S1; S1: LiOH, FeSO4·7H2O and H3PO4 were placed in a reaction kettle, deionized water was added and mixed evenly, and the mixture was treated at 200°C for 16 hours, filtered and dried to obtain an LFP precursor; Among them, the molar mass ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1; S2: The LFP precursor, carbon black and Nb2O5 are fully mechanically mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 550°C-600°C for 18 hours to obtain a modified LFP material; Among them, the mass ratio of LFP precursor to Nb2O5 is 125:1; the mass ratio of LFP precursor to carbon source is 95:1; The heating rate of calcination is 30°C / min, and the annealing rate of calcination is 25°C / min; S3: The modified LFP material, PVDF (KF1100), and conductive agent (Super P) were uniformly mixed in a mass ratio of 97:2:1, coated on a 12 μm aluminum foil, and dried at 120 °C for 12 hours to obtain a positive electrode material.
[0030] Comparative Example 3 is based on Example 1, and conventional LFP material is used as the positive electrode material; S1: LiOH, FeSO4·7H2O and H3PO4 were placed in a reaction kettle, deionized water was added and mixed evenly, and the mixture was treated at 200°C for 16 hours, filtered and dried to obtain an LFP precursor; Among them, the molar mass ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1; S2: The modified LFP material, PVDF (KF1100), and conductive agent (Super P) were uniformly mixed in a mass ratio of 97:2:1, coated on a 12 μm aluminum foil, and dried at 120 °C for 12 hours to obtain a positive electrode material.
[0031] Comparative Example 4 is based on Example 10, but polyethylene glycol is not added to the modified carbon black; S1: LiOH, FeSO4·7H2O and H3PO4 were placed in a reaction kettle, deionized water was added and mixed evenly, and the mixture was treated at 200°C for 16 hours, filtered and dried to obtain an LFP precursor; Among them, the molar mass ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1; S2: Preparation of modified carbon black: (1) Add carbon black to a mixed acid solution (the mass ratio of concentrated sulfuric acid to concentrated nitric acid is 1:8) and ultrasonically disperse it, heat it to 100°C, react for 18 hours, cool it to room temperature, wash it until it is neutral, filter it, and dry it. Ultrasonic disperse it in oxalyl chloride, add N,N-dimethylformamide (the mass ratio of N,N-dimethylformamide to oxalyl chloride is 3:1), stir it at room temperature for 2 hours, wash it with tetrahydrofuran, and dry it to obtain chlorinated carbon black; (2) Add 2 parts of chlorinated carbon black to 25 parts of dichloromethane and ultrasonically disperse it, add 0.12 parts of ferrocene methanol, mix them evenly, add 1.2 parts of triethylamine, heat it to 55°C, react for 18 hours, purify it, and dry it to obtain modified carbon black; The LFP precursor, modified carbon black, Nb2O5 and single-layer Ti3C2MXene material were fully mechanically mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 600°C for 18 hours to obtain a modified LFP material; Among them, the mass ratio of LFP precursor to Nb2O5 is 125:1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 105:1, and the mass ratio of LFP precursor to carbon source is 95:1; The heating rate of calcination is 30°C / min, and the annealing rate of calcination is 25°C / min; S3: The modified LFP material, PVDF (KF1100), and conductive agent (Super P) were uniformly mixed in a mass ratio of 97:2:1, coated on a 12 μm aluminum foil, and dried at 120 °C for 12 hours to obtain a positive electrode material.
[0032] Comparative Example 5 is based on Example 10, but ferrocene is not added to the modified carbon black; S1: LiOH, FeSO4·7H2O and H3PO4 were placed in a reaction kettle, deionized water was added and mixed evenly, and the mixture was treated at 200°C for 16 hours, filtered and dried to obtain an LFP precursor; Among them, the molar mass ratio of LiOH, FeSO4·7H2O, and H3PO4 is 3:1:1; S2: Preparation of modified carbon black: (1) Add carbon black to a mixed acid solution (the mass ratio of concentrated sulfuric acid to concentrated nitric acid is 1:8) and ultrasonically disperse it, heat it to 100°C, react for 18 hours, cool it to room temperature, wash it until it is neutral, filter it, and dry it. Ultrasonic disperse it in oxalyl chloride, add N,N-dimethylformamide (the mass ratio of N,N-dimethylformamide to oxalyl chloride is 3:1), stir it at room temperature for 2 hours, wash it with tetrahydrofuran, and dry it to obtain chlorinated carbon black; (2) Add 2 parts of chlorinated carbon black to 25 parts of dichloromethane and ultrasonically disperse it, add 0.7 parts of polyethylene glycol (molecular weight 400), mix them evenly, add 1.2 parts of triethylamine, heat it to 55°C, react for 18 hours, purify it, and dry it to obtain modified carbon black; The LFP precursor, modified carbon black, Nb2O5 and single-layer Ti3C2MXene material were fully mechanically mixed, placed in a tube furnace, introduced with nitrogen, and calcined at 600°C for 18 hours to obtain a modified LFP material; Among them, the mass ratio of LFP precursor to Nb2O5 is 125:1, the mass ratio of LFP precursor to monolayer Ti3C2MXene is 105:1, and the mass ratio of LFP precursor to carbon source is 95:1; The heating rate of calcination is 30°C / min, and the annealing rate of calcination is 25°C / min; S3: The modified LFP material, PVDF (KF1100), and conductive agent (Super P) were uniformly mixed in a mass ratio of 97:2:1, coated on a 12 μm aluminum foil, and dried at 120 °C for 12 hours to obtain a positive electrode material.
[0033] Testing experiment: (1) Assembly of button battery: The button battery shell uses CR2032 model, the diaphragm uses 18um diaphragm, and the electrode uses a positive electrode with uniform coating. In a glove box filled with argon, the button battery is assembled in the following order: battery shell - place positive electrode - drip electrolyte - place diaphragm - drip electrolyte - place lithium sheet - place gasket spring - battery shell; (2) Test of the first charge and discharge efficiency: The button battery was charged and discharged at 0.2C using a button battery charge and discharge tester (Wuhan Blue Electric, CT2001A), with a voltage range of 1.95-3.5V. The test results are shown in Table 1. (3) Cycle performance test: The button battery was charged and discharged for 50 cycles at 0.2C using a button battery charge and discharge tester (Wuhan Blue Electric, CT2001A). The voltage range was 1.95-3.5V. The test results are shown in Table 1.
[0034] Table 1
[0035] Conclusion: It can be seen from Table 1 that among Examples 1 to 9, Example 1 is the best solution; Comparative Example 1 is based on Example 1, but without the addition of Nb2O5; this results in a decrease in the initial charge and discharge efficiency and cycle performance of the battery, because Nb in Nb2O5 5+ The Fe doping of the unit cell can effectively improve the migration efficiency of lithium ions and improve its cycle performance after a long cycle. Comparative Example 2 is based on Example 1. In S1, no single layer of Ti3C2MXene is added, resulting in a decrease in battery performance. The introduction of a small amount of single layer of MXene material can not only effectively improve the battery conductivity, but also improve the initial charge and discharge efficiency. In addition, a small amount of F on its surface - The O-site unit in the lattice can be doped to enhance the conductivity by suppressing the antisite defect. Comparative Example 3 is based on Example 1, and conventional LFP material is used as the positive electrode material; thus, the first charge and discharge efficiency and cycle performance of the battery are reduced.
[0036] Example 10 is based on Example 1, and the carbon black is modified by polyethylene glycol and ferrocene methanol; wherein polyethylene glycol has good affinity with LiFePO4, and it can improve the dispersibility of other raw materials, improve the structural stability of the LiFePO4 positive electrode material, thereby enhancing the cycle stability and discharge efficiency of the battery. Ferrocene is a highly conductive organic metal compound that can increase the carbonization degree of polyethylene glycol, thereby improving the cycle stability and rate discharge performance of the battery. Comparative Example 4 is based on Example 10, and polyethylene glycol is not added to the modified carbon black; the dispersibility of raw materials such as carbon black is reduced, which reduces the structural stability of the LiFePO4 positive electrode material, thereby reducing the initial charge and discharge efficiency and cycle performance of the battery; Comparative Example 5 is based on Example 10, and ferrocene is not added to the modified carbon black; resulting in a decrease in the carbonization degree of polyethylene glycol, thereby reducing the performance of the battery.
[0037] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.
Claims
1. A method for preparing a positive electrode material for improving the initial charge and discharge of a lithium battery, characterized in that: The steps include: S1: LiOH, Fe S O4·7H2O and H3PO4 were added into deionized water, mixed evenly, and baked to obtain LFP precursor; S2: The LFP precursor, carbon black, Nb2O5 and single-layer Ti3C2MXene material are fully mechanically mixed and calcined to obtain a modified LFP material; S3: The modified LFP material, the binder and the conductive agent are uniformly mixed, applied on an aluminum foil, and dried to obtain a positive electrode material.
2. The method for preparing a positive electrode material for improving the initial charge and discharge of a lithium battery according to claim 1, characterized in that: The molar ratio of LiOH, FeSO4·7H2O and H3PO4 is 3:1:
1.
3. The method for preparing a positive electrode material for improving the initial charge and discharge of a lithium battery according to claim 1, characterized in that: In the LFP precursor, the mass ratio of the LFP precursor to Nb2O5 is (120~125):1, the mass ratio of the LFP precursor to the single-layer Ti3C2MXene material is (100~105):1, and the mass ratio of the LFP precursor to carbon black is (90~95):
1.
4. The method for preparing a positive electrode material for improving the initial charge and discharge of a lithium battery according to claim 1, characterized in that: The mass ratio of the modified LFP material, the binder and the conductive agent is 97:2:
1.
5. The method for preparing a positive electrode material for improving the initial charge and discharge of a lithium battery according to claim 1, characterized in that: The calcination process conditions are: in a nitrogen atmosphere, heating to 550°C-600°C at a rate of 30°C / min and calcining for 18 hours, and the annealing rate is 25°C / min.
6. The method for preparing a positive electrode material for improving the initial charge and discharge of a lithium battery according to claim 1, characterized in that: The carbon black is modified carbon black; the preparation method of the modified carbon black is as follows: (1) adding carbon black to a mixed acid solution for ultrasonic dispersion, heating to 90°C-100°C, reacting for 18-20 hours, cooling to room temperature, washing to neutrality, filtering, drying, ultrasonically dispersing it in oxalyl chloride, adding N,N-dimethylformamide and stirring at room temperature for 2-3 hours, washing with tetrahydrofuran, and drying to obtain chlorinated carbon black; (2) adding chlorinated carbon black to dichloromethane for ultrasonic dispersion, adding ferrocene methanol and polyethylene glycol, uniformly mixing, adding triethylamine, heating to 50°C-55°C, reacting for 18-20 hours, purifying, and drying to obtain modified carbon black.
7. The method for preparing a positive electrode material for improving the initial charge and discharge of a lithium battery according to claim 6, characterized in that: The raw materials of the modified carbon black include the following components: by mass, 1-2 parts of acyl chloride carbon black, 0.1-0.15 parts of ferrocenium methanol, 0.7-1 parts of polyethylene glycol, 0.8-1.2 parts of triethylamine, and 25-30 parts of dichloromethane.
8. The method for preparing a positive electrode material for improving the initial charge and discharge of a lithium battery according to claim 6, characterized in that: The mass ratio of the N,N-dimethylformamide to oxalyl chloride is (3-6):1; the molecular weight of the polyethylene glycol is 200-600.
Citation Information
Cited By
Positive electrode material for improving first charge-discharge efficiency of sodium battery and preparation method of positive electrode material
CN119890271A
